Combustion chemistry of COS and occurrence of intersystem crossing. (1st January 2021) - Zeng, Zhe; Dlugogorski, Bogdan Z.; Oluwoye, Ibukun; Altarawneh, Mohammednoor
Graphical abstract: Highlights: Profiles of experimental species for the oxidation of COS in a jet-stirred reactor operated from 550 K to 1400 K. Arrhenius parameters for the oxidation reaction fitted as a single step process from the direct experimental measurements. Confirmation of the appearance of an intersystem crossing in the oxidation of COS. A new kinetic model that affords good agreement between the experimental and modelling results. Implications for practical applications and future studies. Abstract: This contribution combines results of experiments with kinetic modelling to probe the unusual behaviour of carbonyl sulfide (COS), a sulfur species that frequently arises in fuel systems. The experiments identified CO and SO2 as the primary oxidation products, with no formation of CO2 . The low ignition temperature (<600 K) of COS observed in prior experiments conflicts with the high activation barrier for the reaction COS + O2 → CO2 + SO of 211.3 kJ mol −1 on the traditional triplet reaction surface. We proposed that, this kinetic barrier prompts the reaction to transfer onto the singlet surface through intersystem crossing that allows the process to surmount lower-energy hurdles. By considering the oxidation of COS as a single step reaction, we fitted the Arrhenius parameter for the reaction COS + O2 → CO + SO2 directly from our experimental measurements. The fitted activation energy of 70.1 kJ∙mol −1 agrees with that of 85.4 ± 20.0 kJ∙mol −1 as calculated in literature at the Hartree-Fock level of theory, indicating the appearance of the intersystem crossing process in the oxidation of COS. The reaction mechanism based on this comportment leads to excellent agreement between the kinetic model and the experimentally measured quantities, such as the onset temperature and the conversion profiles of detected species. The proposed kinetic model for the oxidation of COS provides a tool to design both the SOx mitigation processes and industrial systems for safe handling of sulfur impurities in fossil fuels.